Determinants on Environmental Disclosure Moderating by Integrated Corporate Governance - Yuha Nadhirah Qintharah; Fransisca Listyaningsih Utami (Pandawan, 2023)
This will use companies from sector energy and sector goods raw as population companies. Technique taking sample used is non- probability with purposive sampling method. Study this alone using criteria sample appropriate company with specified sector, company publish report possible finances accessed on 2018-2021, required data complete and company no once experienced a delisting during year research. Results sample companies used in the study are as many as 448. Test hypothesis in study this will be tested using the Eviews program. Method research used is moderated regression analysis (MRA) using eviews software. Besides that is, research this do test assumption classic and also test model accuracy to find out which model is most appropriate. Results from study this shows the sample data used to get away in testing assumption classics namely, normality, multicollinearity, heteroscedasticity and autocorrelation. From the results testing hypothesis found that environmental costs have an effect positive against environmental disclosure, international environmental certification does not influential on environmental disclosure, industry sensitivity has an effect positive on environmental disclosure, international corporate governance is capable strengthen influence between environmental cost and environmental disclosure, international corporate governance is capable strengthen influence between international environmental certification and environmental disclosure and international corporate governance is not capable strengthen influence Among sensitivity industry against environmental disclosures.